Monitoring Group Activity of Hamsters and Mice as a Novel Tool to Evaluate COVID-19 Progression, Convalescence, and rVSV-ΔG-Spike Vaccination Efficacy - Melamed, Sharon; Politi, Boaz; Grauer, Ettie; Achdout, Hagit; Aftalion, Moshe; Gur, David; Tamir, Hadas; Yahalom-Ronen, Yfat; Maimon, Shlomy; Yitzhak, Efi; Weiss, Shay; Rosner, Amir; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
COVID-19 pandemic initiated a worldwide race toward the development of treatments and vaccines. Small animal models were the Syrian golden hamster and the K18-hACE2 mice infected with SARS-CoV-2 to display a disease state with some aspects of the human COVID- 19. Group activity of animals in their home cage continuously monitored by the HCMS100 was used as a sensitive marker of disease, successfully detecting morbidity symptoms of SARSCoV-2 infection in hamsters and in K18-hACE2 mice. COVID-19 convalescent hamsters rechallenged with SARS-CoV-2, exhibited minor reduction in group activity compared to naive hamsters. To evaluate rVSV-ΔG-spike vaccination efficacy against SARS-CoV-2, we used the HCMS100 to monitor group activity of hamsters in their home cage. Single-dose rVSV-ΔGspike vaccination of immunized group showed a faster recovery compared to the nonimmunized infected hamsters, substantiating the efficacy of rVSV-ΔG-spike vaccine. HCMS100 offers non-intrusive, hands-free monitoring of a number of home cages of hamsters or mice modeling COVID-19.